ANALYSIS OF CONSUMPTION PATTERNS OF GOODS AND SERVICES IN HOUSEHOLDS DURING THE COVID-19 PANDEMIC: CASE STUDY IN BANDUNG REGENCY: ANALYSIS OF CONSUMPTION PATTERNS OF GOODS AND SERVICES IN HOUSEHOLDS DURING THE COVID-19 PANDEMIC: CASE STUDY IN BANDUNG REGENCY - Hayati, Amelia; Rasyad, Faishal; Anugrah, Mochammad; Putra, Allan Santoso; Khalis, Fahmil; Putri, Aulia Maharani; Rizqi, Ananda Aulia (PT. RANESS MEDIA RANCAGE, 2022)
COVID-19 is a virus that was first discovered in the city of Wuhan, China which spreads through small droplets from the sufferer’s nose or mouth. World Health Organization (WHO) has classified this disease as a global pandemic. The Indonesian government has established several policies to prevent the spread of the COVID-19 virus. This policy harmed the local community activities, such as loss of income, mass layoffs, and significant changes in people’s lifestyles. Consumption is one aspect of life that is influenced by various factors such as income, needs, and the price of goods itself. During epidemics and changes in government policies, the amount of public consumption will also change, including the pattern of public consumption which can change according to many existing factors. A consumption pattern is a picture of the amount, type, and frequency of goods and services consumed by a person or group of people to meet their needs. From consumption patterns, we can see the level of welfare or economic condition of a group from the types of goods and services consumed or the income spent to meet these needs. The results of several studies state that there has been a shift or change in consumption activities for goods and services in Indonesia during and after the COVID-19 pandemic.